Beam-column tests of cold-formed steel elliptical hollow sections. (1st May 2020) - Chen, Man-Tai; Young, Ben
Highlights: 42 beam-column member tests on cold-formed steel elliptical hollow sections were conducted. The specimens were subjected to combined compression and minor axis bending. Predictions from current design methods were compared with test results. The predictions are quite conservative for cold-formed steel elliptical section beam-column members. Abstract: An experimental study on cold-formed steel elliptical hollow section (EHS) beam-columns is described in this paper. Forty-two beam-column members with two different specimen lengths were tested at different eccentricities to investigate the load-moment interaction relationship. The initial geometric imperfections were determined before the formal tests. The ultimate load-carrying capacities and full load-displacement responses are presented and discussed. The design of cold-formed steel EHS subjected to compression plus bending is not covered by the current design specifications. Hence, the beam-column strengths derived from the experimental investigation were used to assess the design predictions by incorporating the equivalent diameter method, the equivalent rectangular hollow section approach and the conventional design methods using equivalent diameter for bending and compressive strength predictions with the interaction curves adopted in the current design rules for structural use of steel. The reliability of these design rules was evaluated. The comparisons reveal that the predictions by these design methods are generally quite conservative and reliable for cold-formed steel EHS subjected to compression plus bending, except that the design method incorporating the equivalent rectangular hollow section approach with the interaction relationship specified in European Code is unreliable.